Role of international network on surveillance and response system leading to malaria elimination: China's engagement in global health - Shenning Lu; Lulu Huang; Lei Duan; Qiuli Xu; Xuejiao Ma; Wei Ding; Duoquan Wang; Shan Lv; Ning Xiao (BMC, 2022)
Abstract China has accumulated multiple practices and experiences in building and enhancing malaria surveillance and response system. As China's engagement into global health has gathered stronger momentum than ever, China together with the Swiss Tropical and Public Health Institute and WHO has organised five sessions of the International Forum on Surveillance-Response System Leading to Tropical Diseases Elimination during 2012-2020, in which malaria elimination has always been one of the hottest topics. In this study, the roles of international network on the surveillance and response system were explored to achieve a global malaria-free goal. China's approach to malaria elimination has demonstrated significance of global collaboration on taking joint prevention and control, and building a worldwide institutional-based network.